Multisystem inflammatory syndrome complicated by pulmonary embolism in a child - L.I. Vakulenko; A.V. Riznyk (Group of Companies Med Expert, LLC, 2023)
Purpose - to present a clinical case of a particular complication of post-COVID multisystem inflammatory syndrome (MIS) - pulmonary embolism (PE) which developed due to primary hereditary thrombophilia in a child for better understanding of the MIS evolution and prognosis in children (MIS-C). Case report. In an 11-year-old boy who previously had no hemorrhagic manifestations, the first symptoms of the disease occurred in the form of fever and a hemorrhagic rash on the lower extremities. Later, he developed signs of respiratory failure, his condition worsened, and bilateral community-acquired viral pneumonia caused by COVID-19 was diagnosed. The child presented with post-COVID MIS manifested as PE, which caused further genetic examinations for hereditary thrombophilia. Primary thrombophilia was detected (F2 gene - prothrombin (20210 G>A) D68.5). Concomitant hereditary pathology was probably the reason for a severe course of the infection and the development of a complication in the form of PE requiring intensive and long-term anticoagulant therapy. Conclusions. In case of PE detection, especially in young patients, examinations to confirm or rule out hereditary or acquired thrombophilia are required, that defines recurrent venous thromboembolism prevention programs. This clinical case report is a contribution to the study on the issues of MIS-C, defining links between pulmonary complications (transient or persistent) and serious sequelae in the future. The research was carried out in accordance with the principles of the Helsinki Declaration. The informed consent of the patient was obtained for conducting the studies. No conflict of interests was declared by the authors.